EFEK MEDIASI KEPUASAN KERJA PADA PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN KABUPATEN PONOROGO - Kadiyanto, Fatarul; Suseno, Y. Djoko; Sutarno, Sutarno (Universitas Slamet Riyadi, 2019)
This research aims to review the influence in welfare between: (1) motivation to work against, job satisfaction (2) discipline against, job satisfaction (3), employee motivation of the performance (4) discipline against, performance (5) job satisfaction with the performance, (6) effect mediation job satisfaction on the influence of the performance, motivation (7) effect mediation job satisfaction on the influence of the performance discipline employees ponorogo. district education officeThe population employees district education office ponorogo years 2019 106. a number of peopleA sample taken by the use of sampling saturated, where is all employees to the internal ponorogo district education which consisted of 106 employees be used as a subject in this research.Data collection techniques using the survey through test. reliability and validityUsing multiple linear regression analysis techniques by test assumptions, classic the, analysis f test and test the coefficients determined. The results of the study conclusions: (1) motivation significant impact on job satisfaction, (2) discipline significant impact on job satisfaction, 3 (3) motivation significant impact on performance, (4) discipline significant impact on performance (5) satisfaction significant impact on performance, (6) satisfaction work mediate influence on the performance of motivation, (7) satisfaction work mediate influence discipline against the employee performance ponorogo district education office .